2018
DOI: 10.3389/fimmu.2018.00490
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demyelination and Axonal Loss Are Reduced in MicroRNA-146a Deficient Mice

Abstract: BackgroundThe cuprizone (CPZ) model of multiple sclerosis (MS) was used to identify microRNAs (miRNAs) related to in vivo de- and remyelination. We further investigated the role of miR-146a in miR-146a-deficient (KO) mice: this miRNA is differentially expressed in MS lesions and promotes differentiation of oligodendrocyte precursor cells (OPCs) during remyelination, but its role has not been examined during demyelination.MethodsMicroRNAs were examined by Agilent Mouse miRNA Microarray in the corpus callosum du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 63 publications
7
58
1
Order By: Relevance
“…After 6 weeks of CPZ treatment, the diet was changed to normal rodent chow for an additional 2, 4, and 6 weeks to examine remyelination. According to a bibliographic investigation before the start of the experiment [13,38,51,56], it was confirmed that both females and males were used to induce the cuprizone-induced model, and the test results were similar in the laboratory. Twenty-six animals were divided into two groups of 13 animals each.…”
Section: Animals and Cuprizone Administrationmentioning
confidence: 88%
See 1 more Smart Citation
“…After 6 weeks of CPZ treatment, the diet was changed to normal rodent chow for an additional 2, 4, and 6 weeks to examine remyelination. According to a bibliographic investigation before the start of the experiment [13,38,51,56], it was confirmed that both females and males were used to induce the cuprizone-induced model, and the test results were similar in the laboratory. Twenty-six animals were divided into two groups of 13 animals each.…”
Section: Animals and Cuprizone Administrationmentioning
confidence: 88%
“…One of the MS-related miRNAs, miR-146a, is differentially expressed in MS lesions and promotes the differentiation of oligodendrocyte precursor cells (OPCs) during remyelination [50]; moreover, it is upregulated during CPZ-induced de-and remyelination [51]. In particular, Martin et al (2018) reported that experimental demyelination and axonal loss are reduced in mice deficient in microRNA-146a and that the number of OPCs is slightly higher in WT mice during remyelination, indicating the complex role of miR-146a during in vivo de-and remyelination [51]. In our results, miR-146a-5p was significantly upregulated in mice subjected to CPZ-induced demyelination, suggesting that it may be a key miRNA involved in the induction of demyelination in CPZ-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, even when the BBB was breached using pertussis toxin (PT), CPZ evoked marked CNS demyelination, gliosis and changes in the abundance of proteoforms involved in metabolism, immune and synaptic functions, without detectable T-cell infiltration (Sen et al, 2019a). Studies have indicated that the apparent failure to trigger a T-cell-mediated CNS immune response is due to CPZ-induced atrophy of the thymus (the organ responsible for T-cell maturation and differentiation) and spleen (the organ of T and B lymphocyte production; Solti et al, 2015;Martin et al, 2018;Sui et al, 2019;Sen et al, 2019a). Two additional effects of CPZ on the integrity and function of the peripheral immune system include an increase in the abundance of splenic arginase-I (a protein expressed by myeloid-derived suppressor cells in spleen) and a decreased abundance of protein disulfide isomerize (a protein required for assembly of the major histocompatibility complex-I; Partridge et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In cuprizone demyelination model, miR‐146a was upregulated during de‐ and remyelination (Martin et al., ). The depletion of miR‐146a protected demyelination and axonal loss (Martin et al., ). These studies then highlight the significance of miRNAs in the treatment of CNS demyelination disease.…”
Section: The Function Of Non‐coding Rnas In Myelinating Cellsmentioning
confidence: 99%
“…In EAE mouse model, the expression of miR-19b is significantly reduced, and application of agomiR-19b may enhance the expression of MBP and CNPase and ameliorate demyelination symptoms (Hu, Hu, Zeng, Xiao, & Yang, 2018). In cuprizone demyelination model, miR-146a was upregulated during de-and remyelination (Martin et al, 2018). The depletion of miR-146a protected demyelination and axonal loss (Martin et al, 2018).…”
Section: Coding Rnas In Myelinating Cellsmentioning
confidence: 99%